2016
DOI: 10.1016/j.cell.2016.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Asprosin, a Fasting-Induced Glucogenic Protein Hormone

Abstract: SUMMARY Hepatic glucose release into the circulation is vital for brain function and survival during periods of fasting and is modulated by an array of hormones that precisely regulate plasma glucose levels. We have identified a fasting-induced protein hormone that modulates hepatic glucose release. It is the C-terminal cleavage product of profibrillin, and we name it Asprosin. Asprosin is secreted by white adipose, circulates at nanomolar levels, and is recruited to the liver, where it activates the G protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
710
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(753 citation statements)
references
References 19 publications
36
710
3
4
Order By: Relevance
“…Phosphorylation of PFK2/FBPase-2 favours its phosphatase activity, enabling it to decrease the production of fructose-2,6-bisphosphate, an allosteric inhibitor of the gluconeogenic enzyme fructose-2,6-bisphosphatase 1 (FBPase-1) 98,99 ; phosphorylated PFK2/FBPase-2 also facilitates the nuclear translocation and consequent functional inactivation of glucokinase (GCK) 100 . These mechanisms might also underlie the stimulatory effect of asprosin (an adipose-derived peptide hormone that activates hepatocellular cAMP–PKA signalling) on HGP 101 . The observation that asprosin stimulated HGP in mice that were fasted for 18 h (REF.…”
Section: Control Of Hepatic Gluconeogenesismentioning
confidence: 99%
“…Phosphorylation of PFK2/FBPase-2 favours its phosphatase activity, enabling it to decrease the production of fructose-2,6-bisphosphate, an allosteric inhibitor of the gluconeogenic enzyme fructose-2,6-bisphosphatase 1 (FBPase-1) 98,99 ; phosphorylated PFK2/FBPase-2 also facilitates the nuclear translocation and consequent functional inactivation of glucokinase (GCK) 100 . These mechanisms might also underlie the stimulatory effect of asprosin (an adipose-derived peptide hormone that activates hepatocellular cAMP–PKA signalling) on HGP 101 . The observation that asprosin stimulated HGP in mice that were fasted for 18 h (REF.…”
Section: Control Of Hepatic Gluconeogenesismentioning
confidence: 99%
“…They showed that plasma asprosin peaks during fasting and induces HGP through the activation of cAMP-PKA pathway [220]. In addition, they reported that insulin-resistant mice and prediabetic humans displayed elevated levels of asprosin [220].…”
Section: Insulin Resistance In the Adipose Tissuementioning
confidence: 99%
“…In addition, they reported that insulin-resistant mice and prediabetic humans displayed elevated levels of asprosin [220]. Blocking asprosin using an antiasprosin monoclonal antibody dampened HGP and normalized glucose and insulin levels in insulin-resistant mice [220]. …”
Section: Insulin Resistance In the Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Chopra and colleagues identified mutations in the gene that encodes profibrillin ( FBN1 ) in patients with NPS; the mutations were found to disrupt the expression of asprosin, the C-terminal cleavage product of profibrillin 2 . Asprosin, which is a 140-amino-acid secreted polypeptide, is abundantly expressed in mature white adipocytes and is thus considered a new adipokine.…”
mentioning
confidence: 99%